Navigating Linguistic Diversity: Indonesian Language Variation and Communication Adaptation among First-Year University Students - Adenia Kusuma Etacho; Aulia Novika; Fahya Dika Aurelia; Muhammad Faruq Zakiuddin; Tamara Putri Kamila (KIRANA : Social Science Journal, 2026)
This study aims to examine the variation in Indonesian language use and the communication adaptation of first-year students within the multicultural environment of Universitas Pembangunan Nasional "Veteran" East Java. The diverse geographical backgrounds of students contribute to variations in language, regional dialects, and local vocabulary that influence daily interactions on campus. This study employed a descriptive quantitative approach using an online survey administered through Google Forms. A total of 15 first-year students from different regions of Indonesia participated as respondents. The collected data were analyzed descriptively to identify language variation, communication barriers, and students' adaptation strategies. The findings indicate that Indonesian serves as the primary medium of communication and effectively facilitates students' adaptation to campus life. Nevertheless, regional dialects and local languages remain frequently used in informal interactions, creating communication challenges, particularly in understanding local vocabulary, humor, and region-specific expressions. To overcome these challenges, students commonly use standard Indonesian, seek clarification from peers, and gradually learn local dialects. These findings suggest that linguistic diversity represents both a challenge and an opportunity for fostering inclusive communication in multicultural higher education. Therefore, strengthening the use of Indonesian as the national lingua franca while preserving regional languages as cultural heritage is essential for promoting effective intercultural communication.